Penerapan Asas Legalitas dalam Pembaharuan Hukum Pidana Indonesia: Studi Kritis Terhadap KUHP Nasional (UU No. 1 Tahun 2023) - Muh. Fadli Faisal Rasyid; Nurasia Natsir (Jurnal Ragam Pengabdian, 2026)
The reform of Indonesian criminal law through the enactment of Law Number 1 of 2023 on the National Criminal Code (KUHP Nasional) marks a historic milestone after more than seven decades of relying on the colonial-era Wetboek van Strafrecht (WvS). One of the most fundamental transformations within the National Criminal Code is the reformulation of the principle of legality, which is no longer confined to written law (lex scripta) but also recognizes the existence of living law within society as a source of criminal law. This article aims to critically analyze the construction of the legality principle in the National Criminal Code, to identify normative tensions between the formal legality principle and the recognition of customary law, and to evaluate the juridical implications for legal certainty, human rights protection, and criminal justice practice in Indonesia. Employing a normative-comparative approach and legal hermeneutic analysis, this study finds that Articles 1(1) and 2 of the National Criminal Code create a normative dualism that potentially generates legal uncertainty in the absence of adequate interpretive guidelines. The article concludes that a conceptual harmonization is necessary between the modernity of criminal law and the values of legal pluralism that characterize Indonesia, including the development of technical regulations clarifying the boundaries and mechanisms for applying living law in judicial practice.